Intrusion detection and avoidance of black and grey hole attacks using AODV protocol based MANET - Shaikh, Uzma; Paul Rajan, Arokia (International Journal of Engineering and Technology, 2017)
Mobile Ad-hoc Network (MANET) is a mobile network which has a large scale of self-directed nodes which is powerful to form a short-term means ofÂ communicationÂ network, without any use of prior communications. Due to its uniqueness like partial resources, varying loopsÂ andÂ shortfall of controlling the networks, these networks are exposed to diverse network layer issues. The â€œAd hoc on demand distance vectorâ€ is a self-starting directing procedure whose security is compromised with the distinct form of attack named as â€œBlack-Holeâ€ and â€œGrey Holeâ€ attacks. This â€œmalicious nodeâ€ publicize as such, it contains the supreme track to the target during the route discovery process and thusÂ interruptÂ the real communication and corrupt network performance. This paper introduces a new method in which a base node is introduced in the network that increases the probability of detecting multiple malicious nodes in the network and further separate them from taking part in any communication. It detects the corrupted nodes andÂ preventÂ it by causing an effectÂ forÂ the communication. The proposed method has been experimented using NS2 and the results found to be efficient.